Tommy e Nonno Orsone - Anania, Stefania (Umanizzazione delle cure in Terapia Intensiva, 2023)
This book was made for children aged 3 to 6 with a loved one who got hospitalized in intensive care. Reading it to the children can help to explain them what is happening to the patient and the rest of the family, recognizing the importance of feelings and fears. It can be used first of all to prepare children for a possible entry into an Intensive Care Unit, accompanied by his family members and health professionals. This book also contains two extra contributions: a small guide for parents and some suggestions for operators (shaped insert with Doctor Owl and Nurse Rabbit). The aim is to create a true "therapeutic alliance", towards the protection of every preschooler from the avoidable pain of magnified worry, loneliness, fear of the unknown. This volume is related to a larger action-research project (MinViTI Project) which aims to improve the psychological well-being of minors who have a family member hospitalized in Intensive Care and was made in collaboration with Progetto Intensiva.it, a scientific initiative promoted and supported by SIAARTI, Aniarti, AAROI-EMAC.